Hemodynamic Instability Secondary to Vasopressin Withdrawal in Septic Shock. (September 2019) - Bissell, Brittany D.; Magee, Carolyn; Moran, Peter; Bastin, Melissa L. Thompson; Flannery, Alexander H.
Rationale: Vasopressors such as norepinephrine are first line for support of mean arterial pressure (MAP) in the management of septic shock. Their use, however, is commonly associated with many adverse events. These detriments frequently trigger the use of alternative, noncatecholamine therapies, including vasopressin. Vasopressin deficiency is a known physiologic consequence of septic shock, and while guidelines recommend vasopressin in addition to norepinephrine, no consensus exists on the duration of deficiency or ideal time of cessation. Studies have suggested that vasopressin discontinuation prior to other vasopressors may lead to hypotension; however, data are limited. This study evaluates the optimal sequence for the discontinuation of vasopressin therapy in septic shock. Methods: This was a 1-year retrospective study of 152 patients admitted to the medical intensive care unit (ICU) with septic shock who received concurrent norepinephrine and vasopressin for vasoactive support. Patients were excluded if death occurred on vasopressors, within 24 hours after discontinuation of vasopressors, or within 48 hours of ICU admission. The primary outcome of hemodynamic instability included incidence of hypotension after vasopressor discontinuation (2 consecutive MAPs < 60 mm Hg), fluid bolus administration, greater than 0.05 μg/kg/min increase in norepinephrine requirements, or addition of an alternative vasopressor. Secondary outcomes included time to hypotension, total vasopressor duration, arrhythmias, mortality, and length of stay. Results: Ninety-one patients met exclusion criteria, resulting in 61 patients for evaluation. Vasopressin was the first vasoactive therapy to be discontinued in 19 patients and last in 42 patients. Baseline characteristics and the use of potentially confounding treatments known to effect MAP were similar between groups. Discontinuation of vasopressin first was associated with a significant increase in hemodynamic instability (74% vs 16.7%, P < .01), with a shorter time to hemodynamic instability (5 vs 15 hours, P < .01). Secondary outcomes were similar. Conclusion: Vasopressin discontinuation prior to cessation of norepinephrine infusion was associated with an increased risk of hemodynamic instability.